1962
DOI: 10.1136/gut.3.1.60
|View full text |Cite
|
Sign up to set email alerts
|

The late prognosis of perforated duodenal ulcer

Abstract: SYNOPSIS One hundred and seventy cases of perforated duodenal ulcer have been followed up after eight to 10 years. Simple suture of the perforation is recommended. The decision to perform elective surgery is best made during the first two years after perforation rather than at the time of the emergency procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Surgical management, which included bowel resection and anastomosis, stoma creation, and closure of perforations, was dependent on the intraoperative findings and to the surgeon's judgment, and the options adopted were similar to those reported in other studies. 1,7,10 The rate of mortality found in our study (22.2%), was comparable to results found in other studies in Africa, as it was found to be 20% in studies done in Nigeria. 10,11 Contrary to results of other studies done in children, 10,11 younger age was not associated with mortality in our sample.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical management, which included bowel resection and anastomosis, stoma creation, and closure of perforations, was dependent on the intraoperative findings and to the surgeon's judgment, and the options adopted were similar to those reported in other studies. 1,7,10 The rate of mortality found in our study (22.2%), was comparable to results found in other studies in Africa, as it was found to be 20% in studies done in Nigeria. 10,11 Contrary to results of other studies done in children, 10,11 younger age was not associated with mortality in our sample.…”
Section: Discussionsupporting
confidence: 90%
“…8,10 More commonly the perforations involved the proximal part of gastrointestinal tract. 6,[11][12][13] 8,14,15 Our observations are also in contrast to studies from western countries where perforations were more common in the distal part. 16,17 It may be noted that then spectrum of perforation peritonitis in India continues to be different from western counterparts.…”
Section: Discussionmentioning
confidence: 62%
“…More commonly the perforations involve the proximal part of the gastrointestinal tract; [ 10 – 13 ] this being in contrast to studies from the western countries, where perforations are common in the distal part [ 14 – 16 ].…”
Section: Discussionmentioning
confidence: 99%